Global Public Goods: A Survey - Buchholz, Wolfgang; Sandler, Todd (Journal of Economic Literature, 2021)
This survey investigates the increasing importance of global public goods (GPGs) in today’s interdependent world, driven by ever-growing, cross-border externalities and public good spillovers. Novel technologies, enhanced globalization, and population increases are among the main drivers of the rise of GPGs. Key GPGs include curbing climate change, instituting universal regulatory practices, eradicating infectious diseases, preserving world peace, discovering scientific breakthroughs, and limiting financial crises. The survey presents a compact theoretical foundation for GPGs, grounded in the provision of public goods. Because countries may be contributors or noncontributors to a particular GPG, coalition formation and behavior play a role, as do strategic interactions between a contributor coalition and other countries. In the survey, recurrent themes include strategic considerations, alternative institutional arrangements, GPGs’ defining properties, new actors’ roles, and collective action concerns. The four properties of GPGs—benefit non-rivalry, benefit non-excludability, aggregator technology, and spillover range—influence the GPGs’ supply prognoses and the need for and form of provision intervention, which may affect the requisite institutional changes. Three representative case studies illustrate how theoretical insights inform policy and empirical tests. Regional public goods are shown to involve a question of subsidiarity and different actors compared to GPGs. (JEL C71, C72, D62, D70, H41, Q54)